2022
DOI: 10.1128/jb.00477-21
|View full text |Cite
|
Sign up to set email alerts
|

Union Is Strength: Target-Based and Whole-Cell High-Throughput Screens in Antibacterial Discovery

Abstract: Antimicrobial resistance is one of the greatest global health challenges today. For over three decades antibacterial discovery research and development has been focused on cell-based and target-based high throughput assays. Target-based screens use diagnostic enzymatic reactions to look for molecules that can bind directly and inhibit the target. Target-based screens are only applied to proteins that can be successfully expressed, purified and the activity of which can be effectively measured using a biochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Considering that disulfide bonds are required for the stability of virulence factors, toxins, antibiotic resistance, and cell envelope biogenesis proteins, lack of disulfide bond formation in many gram-negative pathogens results in virulence attenuation as well as antibiotic and phage susceptibility (6, 7, 21, 23, 45). However, the pathway is not essential for aerobic laboratory growth (17), thus facilitating the development of methods to search for molecules that identify molecules on-target in pathogenic bacteria, also known as target-based and whole cell-based approaches (46). The biosensor plasmids generated in this work could not only help to identify such Dsb inhibitors but also to study the variations of disulfide bond formation found in other bacteria (7, 14).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that disulfide bonds are required for the stability of virulence factors, toxins, antibiotic resistance, and cell envelope biogenesis proteins, lack of disulfide bond formation in many gram-negative pathogens results in virulence attenuation as well as antibiotic and phage susceptibility (6, 7, 21, 23, 45). However, the pathway is not essential for aerobic laboratory growth (17), thus facilitating the development of methods to search for molecules that identify molecules on-target in pathogenic bacteria, also known as target-based and whole cell-based approaches (46). The biosensor plasmids generated in this work could not only help to identify such Dsb inhibitors but also to study the variations of disulfide bond formation found in other bacteria (7, 14).…”
Section: Discussionmentioning
confidence: 99%
“…Combination strategies utilizing both CT-HTS and MT-HTS approaches are on the rise largely because they complement each other by circumventing their limitations of each other [ 24 ] and have been comprehensively discussed by Landeta and Meija-Santana [ 52 ]. Combined assays can help eradicate false positives but can be expensive and time-consuming.…”
Section: Approaches and Strategies For Antibacterial High-throughput ...mentioning
confidence: 99%
“…Several pharmaceutical companies, including Abbott, Bayer, and GlaxoSmithKlin are working on discovering antibiotics that inhibit the growth of whole bacterial cells [30 In this way, the number of hits on the target can be increased, and a greater number o targets for a pathogen's physiological process or pathway can be tested [31]. Antibiotic discovered based on this method are the most marketable because they allow the bio chemical function of the target to be known even if certain elements are unknown sinc they have the advantage of targeting more than one target, but their mode of action (MOA is unknown [26,[32][33][34].…”
Section: Pharmaceutical Companies' Strategies For Using Bacterial Gen...mentioning
confidence: 99%